2012
DOI: 10.1155/2012/584219
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma and Its Stromal Nonimmune Microecosystem

Abstract: In recent years, rapid advances were reached in the understanding of a series of biologic signals influencing cutaneous malignant melanoma (CMM) cells. CMM is in close contact with a peculiar dermal extracellular matrix (ECM). Stromal cells store and release various structural ECM components. The impact on CMM growth and progression is mediated through strong and long-lasting effects of ECM products. This paper summarizes some peculiar aspects of the peri-CMM stroma showing intracytoplasmic loads in Factor XII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…[40][41][42] The refractoriness to the CD-MSC/5FC regimen is also likely to lie in the less efficient uptake of the toxic metabolites as a result of altered tumor-stromal interaction or resistance to apoptosis induction by ECM proteins. 43 Derived tumor cells differently interact with ECM, have altered homocellular tumor-tumor and heterocellular tumorstromal interactions, which subsequently contribute to the adhesion-mediated apoptosis resistance. [44][45][46] Shifted balance between MMPs and their inhibitors (increased expression of MMP-1, -11, -14, -16, TIMP-1 and decreased MMP-2) indicates a different matrix remodeling, 47 potentially leading to anoikis resistance in melanoma cells by mechanism similar to the one suggested by Toricelli et al 48 CD-MSC/5FC exerts potent bystander effect in the cells with functional gap junction intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] The refractoriness to the CD-MSC/5FC regimen is also likely to lie in the less efficient uptake of the toxic metabolites as a result of altered tumor-stromal interaction or resistance to apoptosis induction by ECM proteins. 43 Derived tumor cells differently interact with ECM, have altered homocellular tumor-tumor and heterocellular tumorstromal interactions, which subsequently contribute to the adhesion-mediated apoptosis resistance. [44][45][46] Shifted balance between MMPs and their inhibitors (increased expression of MMP-1, -11, -14, -16, TIMP-1 and decreased MMP-2) indicates a different matrix remodeling, 47 potentially leading to anoikis resistance in melanoma cells by mechanism similar to the one suggested by Toricelli et al 48 CD-MSC/5FC exerts potent bystander effect in the cells with functional gap junction intercellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the correlation of ezrin with S100P or RAGE was not remarkable in metastatic melanoma despite the highly coordinated overexpression of S100P and RAGE. Recent studies revealed a pivotal role of extracellular matrix and integrins in the melanoma cell invasion and metastasis . As ezrin plays an essential role in activating integrins, overexpression of ezrin may be involved, at least in part, in tumor progression of MM …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed a pivotal role of extracellular matrix and integrins in the melanoma cell invasion and metastasis. 32,33 As ezrin plays an essential role in activating integrins, overexpression of ezrin may be involved, at least in part, in tumor progression of MM. 34 In conclusion, our results suggested that the coordinate upregulation of S100P, RAGE and, to a less extent, ezrin may facilitate tumor progression of melanocytic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, immunopathology helps distinguishing among a set of atypical melanocytic neoplasms, and supports attempts to precise CMM staging [4][5][6][7][8][9][10][11]. The aspect of the peritumoral stroma is moreover informative [12,13] . However, predictive markers of therapeutic response are not yet established by these methods so far.…”
Section: Introductionmentioning
confidence: 99%